Differentiated Learning Model For Student with Reading Difficulties - Aldjon Nixon Dapa (JTP - Jurnal Teknologi Pendidikan, 2020)
This research is an analytical-descriptive study which focuses on the characteristics of students with difficulties in reading and the needs for differentiated learning instruction. The result of this study reveals that the prevalence of Students with Difficulties in Reading reaches 9,15% of the total population of students from each elementary school in Tomohon. The most excellent ability in reading comprehension which students have achieved is the level of literal reading. Students who have this level of reading skill can only be found in two elementary schools. Of 10 elementary schools, only students from 4 elementary schools whose reading ability lies on the lowest level, that is understanding vocabulary. In general, students face the difficulties in understanding inference and applying vocabularies. Learning process which has recently used is inadequate to accommodate students’ ability and solve their difficulties. The methods used in class include lectures and assignments. There are two methods, those are Rumpang Method and Glass analysis. The recent condition which students with difficulties in reading face requires immediate and meticulous problem solving. Therefore, teachers need to apply differentiated learning instruction in order to facilitate adaptive learning process suitable for the abilities of students with difficulties in reading.